2019
DOI: 10.25258/ijddt.9.2.30
|View full text |Cite
|
Sign up to set email alerts
|

An Epidemiological, Diagnostic and Therapeutic Study of Giardialamblia in Anbar Province – Iraq

Abstract: This study was carried out to investigate the epidemiology of Giardia lamblia parasites in patients who visited some of the hospitals in Anbar province, which included (Fallujah Teaching Hospital, Ramadi Teaching Hospital, Ramadi Teaching Hospital for Women and Children and Hit Hospital ) during by examining 864 stool samples in a direct examination method, The results revealed the infection rate was 41.7 % and the percentage of infection among males 47.8% is higher than that of females 35.4% with significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Also, it prevents the passage of ions through the cell membrane and affects the biological activities of the parasite by disrupting the acetylcholine which controls all physiological functions of the parasite leading to parasite death (17). Shahatha (25) indicated that saponins have inhibitory efficacy through its effect on enzyme activity.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it prevents the passage of ions through the cell membrane and affects the biological activities of the parasite by disrupting the acetylcholine which controls all physiological functions of the parasite leading to parasite death (17). Shahatha (25) indicated that saponins have inhibitory efficacy through its effect on enzyme activity.…”
Section: Discussionmentioning
confidence: 99%